Humble beginnings? A closer look at social formation during Early Dilmun’s formative phase (c.2200–2050 BC) - Olijdam, Eric (Proceedings of the Seminar for Arabian Studies, 2016)
This contribution highlights developments towards socio-economic and political complexity in Early Dilmun society during the City I period, particularly on Bahrain. This formative phase was highly dynamic, and saw the inception of several aspects fundamental to the developments that took place during the ‘first phase of the second social formation’ (that unfolded during City IIa and which is associated with the creation of an Early State organization). It will be argued that the main impetus for changes in Bahrain’s social fabric during City I was a combination of factional competition, a rapidly expanding and aggregating population, and the investments needed to transform the natural landscape. These changes were not restricted to a small elite, as has been maintained up till now, but seem to have affected all segments of society.